RANCANG BANGUN MESIN PENGUPAS SABUT KELAPA - Sastra Setiawan; Ego fernando; Khadadad Azizi Costacurta; Yang Fitri Arriyani; Masdani Masdani (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Coconut fruit has many benefits, ranging from food, drinks, medicine to cosmetics. Almost all parts can be used such as, roots, wood, coconut leaves, shells, young coconut water and coir. Coir is used for brooms and crafts such as flower pots, hangers, bags and others. The process of stripping coconut husk in Bangka Belitung still uses a lot of traditional tools such as: machetes / machetes, large scissors and crowbars, so the process of stripping coconut husk requires a lot of energy, requires a long time, requires special skills and the risk of work accidents. So, in this final project, a coconut husk peeling machine was designed and made by prioritizing work safety, ergonomics and fast in peeling coconut husk. This coconut husk peeling machine uses 2 rollers in the form of a cylinder with 16 plates attached to the peeling pipe, 12 flat plates and 4 jagged plates. The two rollers rotate in the opposite direction aiming to tear the coconut husk. The engine is driven by a 6.5 PK gasoline combustion motor with a maximum rotational speed of 3600 RPM passed by a sprocket chain to the gearbox input with a sprocket ratio of 1:3 rotational speed and the power coming out of the gearbox 1:40, the power coming out of the gearbox output is passed using a chain transmission and sprocket connected by a rolling roller. This machine is able to peel coconut husk with the longest time of 23 seconds and the fastest time of 13 seconds.